Oxygen Content and Thermodynamic Stability of YBaCo2O6−δ Double Perovskite. (13th February 2018) - Sednev, Anton L.; Zuev, Andrey Yu; Tsvetkov, Dmitry S.
Abstract : The thermodynamic stability of the double perovskite YBaCo2 O6− δ was studied using the coulometric titration technique and verified by measurements of the overall conductivity depending on oxygen partial pressure at a given temperature. As a result, the stability diagram of YBaCo2 O6− δ was plotted. YBaCo2 O6− δ was found to be thermodynamically stable in air at 850°C and higher temperatures, whereas its thermodynamic stability at 900°C is limited by the range of oxygen partial pressures −3.56 ≤ log( p O2 /atm) ≤ −0.14. Oxygen content in YBaCo2 O6− δ slightly decreases at 900°C from 5.035 at log( p O2 /atm) = −0.14 to 4.989 in the atmosphere with log( p O2 /atm) = −3.565 indicating a crucial role which variation of Co +3 /Co +2 ratio plays in its stability. YBaCo2 O6− δ decomposes into the mixture of YCoO3 and BaCoO3− z at the high p O2 stability limit, whereas YBaCo4 O7, BaCo1− x Y x O3− γ, and Y2 O3 were identified as the products of its decomposition at the low p O2 one.